Comparison of primary vaccination regimes for equine influenza: Working towards an evidence‐based regime. (29th January 2014) - Cullinane, A.; Gildea, S.; Weldon, E.
Summary: Reasons for performing study: Vaccination is crucial to the control of equine influenza (EI). The study was conducted in an effort to lay the groundwork for achieving international harmonisation of regulatory requirements based on scientific evidence of performance of different vaccination regimes. Objectives: To evaluate the effectiveness of 3 different primary vaccination regimes: vaccination with the minimal intervals permitted by the racing authorities; vaccination in accordance with the manufacturer's instructions and vaccination with the longest intervals permitted by the racing authorities. Study design: Randomised, prospective clinical trial. Methods: The 55 seronegative unvaccinated horses in this study were subdivided by age and randomly allocated one of the 3 vaccination regimes. All groups were sampled each time a group was vaccinated and 3–5 weeks post vaccination. Horses were vaccinated with a subunit immune stimulating complex‐based vaccine (Equip FT). Antibodies against EI were measured by single radial haemolysis. Results: Lengthening the vaccination intervals increased the immunity gaps between first (V1) and second (V2) doses, and V2 and third dose (V3) but did not inhibit the response to V2 and V3. The response to V2 and V3 was similar irrespective of the regime. Poor responders to V1 were identified in all age groups included in this study but the greatest number of poor responders was among the yearlings. The 2‐ and 3‐year‐old horses responded better to vaccination than the weanlings or yearlings. Conclusions: Longer vaccination intervals permitted by racing authorities increase the periods of susceptibility to EI but they may facilitate strategic vaccination prior to times of increased risk of exposure to virus. The study provides the type of evidence‐based data necessary to commence meaningful discussion of international harmonisation of EI vaccination requirements.